Alkali Metal Yttrium neo‐Pentoxide Double Alkoxide Precursors to Alkali Metal Yttrium Oxide Nanomaterials. Issue 3 (15th March 2016) - Boyle, Timothy J.; Neville, Michael L.; Sears, Jeremiah M.; Cramer, Roger
Abstract: A series of alkali metal yttrium neo ‐pentoxide ([AY(ONep)4 ]) compounds were developed as precursors to alkali yttrium oxide (AYO2 ) nanomaterials. The reaction of yttrium amide ([Y(NR2 )3 ] where R=Si(CH3 )3 ) with four equivalents of H‐ONep followed by addition of [A(NR2 )] (A=Li, Na, K) or A o (A o =Rb, Cs) led to the formation of a complex series of A n Y(ONep) 3+n species, crystallographically identified as [Y2 Li3 (μ3 ‐ONep)(μ3 ‐HONep)(μ‐ONep)5 (ONep)3 (HONep)2 ] (1 ), [YNa2 (μ3 ‐ONep)4 (ONep)]2 (2 ), {[Y2 K3 (μ3 ‐ONep)3 (μ‐ONep)4 (ONep)2 (η ξ ‐tol)2 ][Y4 K2 (μ4 ‐O)(μ3 ‐ONep)8 (ONep)4 ]η x ‐tol]} (3 ), [Y4 K2 (μ4 ‐O)(μ3 ‐ONep)8 (ONep)4 ] (3 a ), [Y2 Rb3 (μ4 ‐ONep)3 (μ‐ONep)6 ] (4 ), and [Y2 Cs4 (μ6 ‐O)(μ3 ‐ONep)6 (μ3 ‐HONep)2 (ONep)2 (η x ‐tol)4 ]tol (5 ). Compounds1–5 were investigated as single source precursors to AYO x nanomaterials following solvothermal routes (pyridine, 185 o C for 24 h). The final products after thermal processing were found by powder X‐ray diffraction experiments to be Y2 O3 with variable sized particles based on transmission electron diffraction. Energy dispersive X‐ray spectroscopy studies indicated that the heavier alkali metal species were present in the isolated nanomaterials. Abstract : A series of alkali metal yttrium neo ‐pentoxide ([AY(ONep)4 ]) compounds were crystallographically characterized from the reaction of yttrium amide ([Y(NR2 )3 ] where R=Si(CH3 )3 ) with four equivalents of H‐ONep followed by addition of [A(NR2 )] (A=Li, Na, K) or A o (A o =Rb, Cs (product shown)). These novel precursors were used to produce mixed A x YO n nanomaterials.